Transformation of Islamic Education: Exploring Historical Roots and Its Development in Indonesia - Zaenal Arifin; Jalaluddin; Syifa; Yeyen; Illman; Attar (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines the development of Islamic education in Indonesia from the time of the Islamic kingdom, Dutch colonialism, Japanese colonialism, to the Old Order and New Order eras. During the Islamic kingdom, Islamic education developed through traditional institutions such as Islamic boarding schools, which played an important role in the spread of Islamic teachings. This study shows that Islamic education in Indonesia has gone through different stages, from traditional Islamic boarding schools to modern educational institutions, reflecting local conditions and adaptation to global challenges. In addition, this study also discusses organizations, institutions, and figures who have contributed greatly to the development of Islamic education in Indonesia, and reviews the Islamic education system in relation to national education. The results of this study are expected to provide a deep understanding of the dynamics of Islamic education in Indonesia and its contribution to the development of the national education system